QARAQALPAQSTANDA MEKTEP GEOGRAFIYASÍ SABAǴÍN OQÍTÍWDÍŃ JETISKENLIKLERI HÁM KEMShILIKLERI - Uzakbaev, Koblan Kewnimjay ulı (SCIENCE and SOCIETY, 2026)
This article describes the achievements and shortcomings in teaching school geography in Uzbekistan, as well as in Karakalpakstan.